AN OSTEOMETRIC STUDY OF THE SKULL OF ADULT BEETAL GOAT - S. Din; S. Masood; H. Zaneb; H. Rehman; S. Ashraf; I. Khan; M. Shah; S. A. Hadi (Journal of Animal and Plant Sciences, 2020)
Beetal is a large-sized goat breed in Pakistan, produce an average from 1.5 to 3 liters of milk on daily basis and is known for several features, including heat tolerance, prolificacy, and multi-purpose utilization. In spite of such remarkable features, gross anatomical characteristics of these goats are still not explored. Therefore, this preliminary study was designed to measure clinically important landmarks in the skull of adult Beetal goat in both sex as an attempt to provide a baseline data. Skulls (n=20) of Beetal goats (10 each of males and females) were used in the study. The skulls of both sexes were collected from apparently clinically healthy goats after slaughtering at an abattoir and treated according to the hot water maceration procedures. Biometric parameters were measured with the help of a digital vernier calliper. Descriptive statistics of the measured skull parameters did not show statistically significant differences between male and female adult Beetal goat. However, the studied parameters demonstrated variations from previously reported data in other breeds of goat and sheep. The measured anatomical standards are of clinical significance and will aid in regional nerve blocks and archaeological studies.
Keywords: Beetal Goat; Skull; Morphometry; Sexual dimorphism